PENGABDIAN MASYARAKAT SOSIALISASI DAN EDUKASI PENCEGAHAN RAWAT ULANG PASIEN TB PARU DI RUMAH DEWI SRI KARAWANG - Sumitro, Sumitro; Asih, Okti Rahayu; Desrianti, Cindy; Asih, Mutiara Puspita (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to socialize counseling using the patient and family empowerment module in preventing rehospitalization of pulmonary TB patients at Dewi Sri Karawang Hospital. This community service uses interview and education methods to prevent rehospitalization of pulmonary TB in post-hospitalization patients who seek outpatient treatment at the pulmonary clinic of Dewi Sri Karawang Hospital. The module used is a family and patient empowerment education module on preventing rehospitalization of pulmonary TB patients consisting of seven themes, namely the definition of pulmonary TB, family experience in caring for pulmonary TB patients, the impact felt when caring for patients, what will happen if pulmonary TB is not treated immediately and family efforts so that patients do not relapse or rehospitalize. The results of the community service showed an increase in knowledge and understanding of families who have family members undergoing pulmonary TB treatment at home